Development of a selection and appraisal policy and strategy for the Meycauayan College Archives - Diaz, Mary Jane D.
Meycauayan College, in anticipation of its centennial celebration, embarked on the establishment of its archival repository in anticipation of its centennial celebration. This project endeavors to address the critical need for a systematic and comprehensive Selection and Appraisal Policy and Strategy for the archives of Meycauayan College that will guide the acquisition, evaluation, and preservation of institutional materials, ensuring that the Archives effectively fulfill its role as custodian of Meycauayan College’s heritage.